INSTYTUCJA MEDIACJI KARNEJ W PRAWIE POLSKIM - Pachnik, Karol (Zeszyty Prawnicze, 2016)
THE INSTITUTION OF PENALTY MEDIATION IN POLISH LAW Summary The institution of penalty mediation is underestimated form of resolving disputes. Mediation is a agreement between parties in the presence of mediator. This article presents main functions of mediation, which become a another way of resolving disputes, main advantages of mediation for example: speed procedure, smaller costs and effectiveness. Advantages of penalty mediation on the one hand are beneficial for victim and on another hand is also beneficial for defendant. Polish state of law don’t realize this roles of mediation so this part of law should be change. Effectiveness of penalty mediation confirming all statistics in many countries (UE and USA) but this conclusions are hard to prove. This article present in spite of decreased role of penalty mediation, admission this form of mediation as a more effectiveness form. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />